Simulation and order picking in a very-narrow-aisle warehouse. Issue 1 (1st January 2018) - Burinskienė, Aurelija; Davidavičienė, Vida; Raudeliūnienė, Jurgita; Meidutė-Kavaliauskienė, Ieva
Abstract: The revolution of information brought new possibilities for the business organisations: new management methods for managing supply chains, logistic processes and warehouses appear as well as innovative process management methods in the sense of knowledge management. The order picking process in the warehouse should be emphasised as one of the most laborious activities, since it consumes ∼55% of the warehouse labour activities. This study pays special attention to the order picking process in a very-narrow-aisle (V.N.A.) warehouse, with the aim to identify solutions for the reduction of total travel distance and costs. The methods of the scientific literature analysis and synthesis simulation were applied. The results of the simulation confirmed the application of a pick-by-article strategy that is implemented with 'seed' sorting by order solution in low-income countries.